2022
DOI: 10.1007/s10719-022-10076-6
|View full text |Cite
|
Sign up to set email alerts
|

Structural determination of the lipid A from the deep-sea bacterium Zunongwangia profunda SM-A87: a small-scale approach

Abstract: Zunongwangia profunda SM-A87 is a deep-sea sedimentary bacterium from the phylum Bacteroidetes, representing a new genus of Flavobacteriaceae. It was previously investigated for its capability of yielding high quantities of capsular polysaccharides (CPS) with interesting rheological properties, including high viscosity and tolerance to high salinities and temperatures. However, as a Gram-negative, Z. profunda SM-A87 also expresses lipopolysaccharides (LPS) as the main components of the external leaflet of its … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 48 publications
0
6
0
Order By: Relevance
“…Likewise, Cellulophaga lipid A also carries unsaturated acyl chains, which is known to be a characteristic adopted by bacteria to increment the outer membrane fluidity by decreasing the lipid packing [37] . Worth mentioning is also the high content of odd‐numbered (15 and 17 carbon atoms) and branched acyl chains of the Cellulophaga lipid A that was a characteristic often associated with other bacteria of the Bacteroidetes phylum [38–42] . Another peculiarity was the occurrence of hydroxylated acyl chains as secondary substituents of the reducing glucosamine, which in parallel supported the hypothesis of a 3+3 symmetry of the acyl chains in the hexa‐acylated lipid A forms that were detected as minor components of Cellulophaga LPS.…”
Section: Discussionmentioning
confidence: 88%
“…Likewise, Cellulophaga lipid A also carries unsaturated acyl chains, which is known to be a characteristic adopted by bacteria to increment the outer membrane fluidity by decreasing the lipid packing [37] . Worth mentioning is also the high content of odd‐numbered (15 and 17 carbon atoms) and branched acyl chains of the Cellulophaga lipid A that was a characteristic often associated with other bacteria of the Bacteroidetes phylum [38–42] . Another peculiarity was the occurrence of hydroxylated acyl chains as secondary substituents of the reducing glucosamine, which in parallel supported the hypothesis of a 3+3 symmetry of the acyl chains in the hexa‐acylated lipid A forms that were detected as minor components of Cellulophaga LPS.…”
Section: Discussionmentioning
confidence: 88%
“…The results suggest that the growth medium influences the lipid A profiles, especially concerning the HexN modification. The lipid A profiles of A. xylosoxidans isolates AC011, AC036, AC061, AC064, and AC080 and Achromobacter insuavis AC054 were also examined from preparations using large-scale cultures in LB and treated to extract the lipid A as previously described ( 63 ) (Fig. S1).…”
Section: Resultsmentioning
confidence: 99%
“…Briefly, an aliquot of each pellet (~1 mg) was washed with 500 μL of chloroform-methanol (1:2, vol/vol) and then with 500 μL of chloroform-methanol-water (3:2:0.25, vol/vol/vol), followed by several steps of centrifugation (1,200 × g , 30 min). Then, 500 μL of isobutyric acid acid–1 M ammonium hydroxide (5:3, vol/vol) was added to pellets and left at 100°C for 1 h. Upon centrifugation (1,200 × g , 30 min), the supernatants were collected, lyophilized, and washed several times with methanol, followed by a wash with chloroform-methanol-water (3:1.5:0.25, vol/vol/vol) ( 63 ). At this stage, the lipid A fractions were divided into four aliquots, three of which were chemically derivatized to analyze their lipid and sugar contents (see below), whereas the other one was prepared for MALDI-TOF MS analysis and mixed with a matrix solution of 2,4,6-trihydroxyacetophenone (THAP) in methanol–0.1% trifluoroacetic acid–acetonitrile (7:2:1, vol/vol/vol) at a concentration of 75 mg/mL.…”
Section: Methodsmentioning
confidence: 99%
“…By contrast, the presence of heptoses in FA fecal LPS suggested the presence of LPS from Gamma-proteobacteria, and possibly from the Enterobacteriaceae family whose blooming in the human gut typically leads to the instauration and persistence of an inflammatory state (Di Lorenzo et al, 2019;Di Lorenzo et al, 2022). Likewise, fatty acid compositional analyses disclosed the presence of the typical pattern of Bacteroides LPS in CT fecal LPS (Weintraub et al, 1989;Vatanen et al, 2016;Jacobson et al, 2018;Di Lorenzo et al, 2020;Pither et al, 2022b) whereas 12:0, 14:0, 14:0(3-OH) fatty acids were also identified in some FA fecal LPS, which might be considered instead a signature of Gammaproteobacteria (Di Lorenzo et al, 2019) (Supplementary Figure S2).…”
Section: Structural Features Of Gm-derived Lps Are Different In Fa Ch...mentioning
confidence: 99%
“…Moreover, it was possible to promptly associate these peaks to Bacteroides-derived lipid A as in all MS spectra (Figure 2) two main clusters of peaks were detected and matched with [M-H] − mono-phosphorylated penta-acylated (at about m/z 1,659) and tetra-acylated lipid A species (at about m/z 1,419), in agreement with previous studies on Bacteroides sp. lipid A (Weintraub et al, 1989;Vatanen et al, 2016;Jacobson et al, 2018;Di Lorenzo et al, 2020;Pither et al, 2022b). Moreover, each of these groups of peaks was characterized by the occurrence of mass differences of 14 amu (a-CH 2unit) that is diagnostic of the presence of lipid A species…”
Section: Gm-derived Lipid a Mass Spectral Profiles Are Diverse Betwee...mentioning
confidence: 99%